The effect of zikr therapy on family caregivers anxiety during femur fracture sugery - Khasanah, Dewi Nur; Pribadi, Dimas Ria Angga; Dewi, Kenwi Hasta (Science Midwifery, 2025)
Fracture surgery is a significant stressor that may trigger anxiety, not only in patients but also in family members waiting during the procedure. Effective anxiety management can be supported through non-pharmacological interventions. The purpose of this study is to investigate the effect that zikr spiritual treatment has on the anxiety levels of the families of patients who are undergoing surgery to repair a fractured femur. A quasi-experimental strategy, specifically a group pre-test and post-test design that contrasts the intervention group with the control group, is used in this quantitative study design. There were a total of forty-two participants in this study. Of these forty-two participants, twenty-one were assigned to the intervention group, while the other twenty-one were assigned to the control group. The State-Trait Anxiety Inventory-Y (STAI-Y) scale was utilized to assess the degree of anxiety in the intervention and control groups both before to and during the intervention. In the intervention group, zikr therapy was administered for a duration of 10 minutes. The Wilcoxon test results indicated a p-value of 0.000 (p < 0.05) in the intervention group and a p-value of 0.083 (p > 0.05) in the control group. The Mann-Whitney test produced a p-value of 0.000 (p < 0.05), which provided evidence that zikr treatment had a substantial impact on the intervention group and that there was a significant difference in anxiety levels between the control group and the intervention group. Zikr therapy has been shown to be effective in reducing anxiety. These findings indicate that zikr therapy may serve as a valuable non-pharmacological approach to managing anxiety. Further studies are recommended to explore its long-term effects and broader applicability in different clinical contexts.